A meta-analysis of deep hypothermic circulatory arrest alone versus with adjunctive selective antegrade cerebral perfusion - Tian, David H.; Wan, Benjamin; Bannon, Paul G.; Misfeld, Martin; LeMaire, Scott A.; Kazui, Teruhisa; Kouchoukos, Nicholas T.; Elefteriades, John A.; Bavaria, Joseph E.; Coselli, Joseph S.; Griepp, Randall B.; Mohr, Friedrich W.; et al. (Annals of Cardiothoracic Surgery, 2013)
Introduction: Recognizing the importance of neuroprotection in aortic arch surgery, deep hypothermic circulatory arrest (DHCA) now underpins operative practice as it minimizes cerebral metabolic activity. When prolonged periods of circulatory arrest are required, selective antegrade cerebral perfusion (SACP) is supplemented as an adjunct. However, concerns exist over the risks of SACP in introducing embolism and hypo- and hyper-perfusing the brain. The present meta-analysis aims to compare postoperative outcomes in arch surgery using DHCA alone or DHCA + SACP as neuroprotection strategies. Methods: Electronic searches were performed using six databases from their inception to January 2013. Two reviewers independently identified all relevant studies comparing DHCA alone with DHCA + SACP. Data were extracted and meta-analyzed according to pre-defined clinical endpoints. Results: Nine comparative studies were identified in the present meta-analysis, with 648 patients employing DHCA alone and 370 utilizing DHCA + SACP. No significant differences in temporary or permanent neurological outcomes were identified. DHCA + SACP was associated with significantly better survival outcomes (P=0.008, I2=0%), despite longer cardiopulmonary bypass time. Infrequent and inconsistent reporting of other clinical results precluded analysis of systemic outcomes. Conclusions: The present meta-analysis indicate the superiority of DHCA + SACP in terms of mortality outcomes.